2008
DOI: 10.1002/adsc.200700613
|View full text |Cite
|
Sign up to set email alerts
|

Density‐Dependent Formation of the Pure trans‐Isomer of the Unsaturated Alcohol by Selective Hydrogenation of Citral in Supercritical Carbon Dioxide

Abstract: Selective hydrogenation of citral to unsaturated alcohol [geraniol (trans) + nerol (cis)] was carried out in supercritical carbon dioxide (scCO 2 ) using an MCM-41 supported plantinum catalyst (1 wt% Pt). A remarkable rate of isomerization of the unsaturated alcohol [nerol (cis) to geraniol (trans)] during the hydrogenation of citral was achieved simply by tuning the density of CO 2 . Optimum reaction conditions were developed to obtain only geraniol (trans) with a selectivity of 98.8% and citral conversion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In scCO 2 the reaction kinetics exhibited a first-order reaction rate i.e. for limonene 17a and citral 31 hydrogenations. The obtained results indicate that the hydrogenation of the first double bond is always faster in one phase than in two phases as presented in Table 1.…”
Section: The Effect Of Total Pressure On the Reaction Outcomementioning
confidence: 95%
“…In scCO 2 the reaction kinetics exhibited a first-order reaction rate i.e. for limonene 17a and citral 31 hydrogenations. The obtained results indicate that the hydrogenation of the first double bond is always faster in one phase than in two phases as presented in Table 1.…”
Section: The Effect Of Total Pressure On the Reaction Outcomementioning
confidence: 95%
“…In scCO 2 the reaction kinetics exhibited a firstorder reaction rate i.e. for limonene, 10 b-myrcene 27 and citral 35 hydrogenation. Summarising, it can be stated that the pressure of CO 2 strongly affects the reaction conditions, and at lower total pressure (12.5 MPa) reactions were carried out in biphasic (liquid + gas) conditions while a total pressure of 16 MPa shifted the reaction mixture towards a one-phase region.…”
Section: The Catalyst Activitymentioning
confidence: 97%
“…scCO 2 was shown to be a suitable reaction medium for the highly efficient hydrogenation of citral using monometallic Pt and bimetallic PteRu supported on MCM-48 as catalysts at 323 K (Scheme 24) [80]. The Pt catalyst was found to predominantly form unsaturated alcohols geraniol 74 and nerol 75, whereas the addition of Ru to the Pt considerably changed the selectivity for citronellal 70.…”
Section: Hydrogenation Of Citralmentioning
confidence: 98%
“…Selective hydrogenation of citral to unsaturated alcohols 74 and 75 in scCO 2 was carried out using Pt catalyst supported on another mesoporous material, MCM-41 [83]. It was found that nerol 75 can isomerize into β-Myrcene 7 SCHEME 23 Hydrogenation of myrcene.…”
Section: Hydrogenation Of Citralmentioning
confidence: 99%